Towards urban un-sustainability in Europe? An indicator-based analysis - Marjo Kasanko; Jose I. Barredo; Carlo Lavalle; Valentina Sagris (European Regional Science Association (ERSA), 2005)
In this article we analyse the relationship between urban land use development and population density in fifteen European urban areas. In the last 20 years the extent of built-up areas in Europe has increased by 20%, exceeding clearly the 6% rate of population growth over the same period. This is one of the consequences of unsustainable development patterns in large areas of Europe. In order to illustrate such unsustainable process we show five sets of indicators on built-up areas, residential land use, land taken by urban expansion, population density and how the population takes up the built-up space.The results show that analysing urban land use development necessitates the use of complementary indicators. The built-up areas have grown considerably in a sample of 15 European cities. The most rapid growth dates back to 1950s and 1960s. The annual growth pace has slowed down in the 1990s to 0.75 %. In half of the studied cities over 90% of all new housing areas built after the mid-1950s are discontinuous urban developments. This trend is increasing the use of private car and fragmentation of natural areas among others negative effects. When putting these findings into the context of stable or decreasing urban population, it is clear that the structure of most of European cities has become less compact, which demonstrates a de-centralisation process of urban land uses. We close by discussing on one hand the common urban land use and population density trends and on the other hand differences between the studied cities. Although most studied urban areas have experienced dispersed growth, as a result of the analysis we divide the cities in three groups: - compact cities,- cities with looser structures and lower densities,- and cities in the midway between the extremes.
Keywords: 330